Knowledge, attitudes, and practices of Australian allied hearing-healthcare professionals: survey on comorbid hearing loss and cognitive impairment - Jayakody, Dona M. P.; Je, Eunkyeong Grace; Livings, Isabelle; McIlhiney, Paul; Trevenen, Michelle; Kekez, Damir; Mavaddat, Nahal (Frontiers in Medicine, 2024)
Purpose As hearing loss is a modifiable risk factor of dementia, allied hearing-healthcare professionals (AHHPs) frequently see older patients who are affected by both conditions. However, little is known about how well Australian AHHP’s understand the complexities of providing care to patients with comorbid hearing loss and dementia, as well as their associated views and practices. Thus, the current study used a survey to explore the knowledge, attitudes, and practices (KAPs) of Australian AHHPs in managing comorbid patients. Materials and methods A cross-sectional design was used, wherein a KAP survey was developed and distributed to eligible AHHPs via Qualtrics. Data were analysed with descriptive statistics and binary logistic regression. Results 101 Australian AHHPs met inclusion criteria (2.5% of approximately 4,000 invited AHHPs), and participated in the study. Although participants generally possessed a high level of knowledge for the association between hearing loss and cognitive impairment, their specific knowledge and practices in relation to cognitive screening tests and referral pathways was limited. Participants also expressed mostly positive attitudes towards their role in assisting patients with comorbid hearing loss and dementia. Furthermore, our results suggested that some KAPs relevant to comorbid patients differed based on sex, qualification, and ethnicity. Conclusion This study identified gaps in the knowledge and practices of Australian AHHPs with regard to the complexities of addressing comorbid cognitive impairment and hearing loss. These findings will help to develop training programs to empower AHHPs to deliver optimal healthcare services to comorbid patients.